The investigation of the coal ignition temperature and ignition characteristics in an oxygen-enriched FBR. (1st November 2016) - Chao, Junnan; Yang, Hairui; Wu, Yuxin; Zhang, Hai; Lv, Junfu; Dong, Weiguo; Xiao, Naiyou; Zhang, Keda; Xu, Chunxia
Abstract: Oxygen-enriched circulating fluidized bed (CFB) technology is considered as one of the low carbon emission power generation technologies. By recycling the flue gas into the furnace, the CO2 concentration in the exhaust gas can reach over 90%. The coal ignition temperature and ignition characteristics are important factors for boiler design and for choosing the feeding temperature during the transition from air-firing to oxy-firing. The ignition and combustion processes of five types of coal under four different atmospheres (air, O2 27%, O2 40%, O2 53%) were measured in a laboratory scale fluidized bed reactor (FBR) with an under-bed preheat system. Using thermocouples and a gas analyzer, the changes in bed temperature and the concentrations of different components, such as O2, CO2 and CO, in flue gas were directly measured to determine the coal ignition temperature, Ti F . It was found that Ti F decreases with increasing O2 concentration. At lower bed temperatures, two-stage ignition processes were observed in certain ranges of initial bed temperature and oxygen concentration. The influence of initial bed temperature on volatile release and the SO2 emission in the ignition processes were also discussed.